A kinetic resolution strategy for the synthesis of chiral octahedral NHC–iridium(iii) catalysts. Issue 43 (8th May 2019) - Manguin, Romane; Pichon, Delphine; Tarrieu, Robert; Vives, Thomas; Roisnel, Thierry; Dorcet, Vincent; Crévisy, Christophe; Miqueu, Karinne; Favereau, Ludovic; Crassous, Jeanne; Mauduit, Marc; Baslé, Olivier
Abstract : The transmetalation reaction of a chiral-bidentate NHC–silver complex to racemic [lr(μ-Cl)(ppy)2 ]2 operates with kinetic resolution leading to chiral octahedral NHC–iridium(iii ) complexes and enantio-enriched bis-cyclometalated iridium(iii ) complexes. Abstract : The transmetalation reaction of a chiral-bidentate NHC–silver complex to racemic [Ir(μ-Cl)(ppy)2 ]2 operates with kinetic resolution leading to chiral octahedral NHC–iridium(iii ) complexes and enantio-enriched bis-cyclometalated iridium(iii ) complexes. The iridium(iii ) complexes demonstrated efficient catalytic activities in intermolecular [2+2] photocycloaddition reactions and in asymmetric Friedel–Crafts alkylations, respectively.